External cervical resorption: a three‐dimensional classification. (13th September 2017) - Patel, S.; Foschi, F.; Mannocci, F.; Patel, K.
Abstract: This article describes a novel three‐dimensional classification for external cervical resorption (ECR). The European Society of Endodontology and American Association of Endodontists & American Academy of Oral & Maxillofacial Radiology position statements advise that Cone beam computed tomography should be considered for the assessment and/or management of root resorption if it appears to be clinically amenable to treatment following clinical and conventional radiographic examination. The new classification takes into account the ECR lesion height (1: at CEJ level or coronal to the bone crest (supracrestal), 2: extends into the coronal third of the root and apical to the bone crest (subcrestal), 3: extends into the mid‐third of the root, 4: extends into the apical third of the root), circumferential spread (A: ≤90° B: ≤180° C: ≤270° D: >270°) and proximity to the root canal (d: lesion confined to dentine, p: probable pulpal involvement), thus classifying ECR in three dimensions. At present, there is no classification to accurately describe ECR. This novel and clinically relevant three‐dimensional classification should allow effective and accurate communication of ECR lesions between colleagues. It will also allow the effect of the nature of ECR on the outcome of treatment to be assessed objectively.